Chronic obstructive pulmonary disease is associated with higher recurrence rates of atrial fibrillation following catheter ablation - Ree Lu; Devin Skoll; Ahmed Y. Gasmelseed; Geoffrey A. Rubin; Elaine Y. Wan; Amardeep S. Saluja; Jose M. Dizon; Angelo B. Biviano; Hasan Garan; Hirad Yarmohammadi (Indian Pacing and Electrophysiology Journal)
Background: Patients with atrial fibrillation (AF) and chronic obstructive pulmonary disease (COPD) are at increased risk of cardiovascular mortality compared to patients with AF alone. Consequently, employing rhythm control strategies such as AF catheter ablation could offer substantial benefits to patients with COPD. However, the impact of COPD on AF ablation outcomes is not well established. Methods: In this single-center case control study, we retrospectively analyzed 200 patients with AF and COPD, 52 of whom underwent AF catheter ablation. Those who underwent ablation were matched with a control group of patients with AF but without COPD who underwent ablation. Ablation outcomes were compared between the groups. Univariate and multivariable analysis were conducted for prediction of AF recurrence. Results: Compared to the controls, cases with COPD were more likely to have AF recurrence following catheter ablation (OR 13.42, P-value = 0.0001). Multivariable analysis revealed predictors of AF recurrence following catheter ablation included decreased use of loop diuretics and amiodarone. Patients with severe or very severe COPD were more likely to have left atrial enlargement than patients with mild or moderate COPD (OR 2.28, P-value = 0.026). Conclusion: Patients with AF and COPD were more likely than patients with AF but without COPD to experience AF recurrence following catheter ablation. Predictors of AF recurrence included decreased use of loop diuretics and amiodarone. Our study demonstrates that while ablation in patients with COPD is safe, ablation in patients with COPD is associated with higher AF recurrence rates.